How leaders ‘Strength of Heart’ and ‘Strength of Will’ enhance team performance - Rego, A.; Simpson, A. V.; Pina e Cunha, M.; Silard, A.; Oliveira, E. A. da S.; Mamedio, D. F. (Human Performance, 2024)
We investigate the influence of leaders’ dispositional compassion on team development and performance through two studies. In the first multi-source study (n = 154 team leaders), leaders’ dispositional compassion is found to be associated with improved team performance through the adoption of helping behaviors aimed at developing team capabilities. This relationship is moderated by leaders’ perseverance, suggesting that compassionate leaders transition from being inclined to help to actually helping only when they also demonstrate perseverance. In the second multi-source longitudinal study (n = 52 team leaders), we find support for the notion that the positive effect of leaders’ dispositional compassion on team development-helping behaviors is conditional on leaders’ perseverance, thus reinforcing our findings from the first study. We suggest that although dispositional compassion, a “strength of heart,” is a well-known predictor of helping, the feelings and intentions of compassion do not guarantee helping behaviors. Translating these feelings and intentions into compassionate behaviors requires perseverance – a “strength of will.” Hence, our study indicates that leaders’ dispositional compassion is not just a potential humanizing force but also positively correlates with team performance. However, the impact of leaders’ dispositional compassion on team performance only emerges through perseverance in the face of challenges.